NILAI ESTETIS RIAS DAN BUSANA TARI TANI MELATI DESA KALIPRAU SANGGAR SENI KALOKA KABUPATEN PEMALANG - Mahesa, Gessila Siva; Indriyanto, R (JADECS (Journal of Art, Design, Art Education & Cultural Studies), 2021)
Abstract: Make-up are visual aspects in the elements of dance, which means make-up or grooming and dressing aimed at inviting the audience's attention to enjoy and interpret the content of dance offerings. The aesthetic value of the make-up and clothing of Tani Melati Dance includes the appearance value, the content or meaning value, the expression value of each form, process, color that combines the combination of results of jasmine flower ronce as village branding  in realizing the purity of jasmine sambac and the activities of jasmine farmers. Key Words: Aesthetic Value, Make-up, Tani Melati Dance  Abstrak: Rias dan busana adalah aspek visual dalam unsur elemen tari yang berarti berias atau dandan dan berbusana yang bertujuan untuk mengundang perhatian penonton untuk menikmati dan menginterpretasikan isi sajian tari. Nilai esteis rias dan busana Tari Tani Melati meliputi nilai kesan penampilan, nilai isi atau makna, nilai pengungkapan dari setiap perpaduan bentuk, proses, warna yang menggabungkan perpaduan dari hasil ronce bunga melati sebagai branding desa dalam mewujudkan kemurnian Jasmine Sambac dan aktivitas petani melati. Kata kunci: Nilai Estetis, Rias dan Busana, Tari Tani Melati